Organisational models in primary health care to manage chronic conditions: A scoping review. (20th October 2021) - Longhini, Jessica; Canzan, Federica; Mezzalira, Elisabetta; Saiani, Luisa; Ambrosi, Elisa
Abstract: Chronic diseases are increasing incessantly, and more efforts are needed in order to develop effective organisational models in primary health care, which may address the challenges posed by the consequent multimorbidity. The aim of this study was to assess and map methods, interventions and outcomes investigated over the last decade regarding the effectiveness of chronic care organisational models in primary care settings. We conducted a scoping review including systematic reviews, clinical trials, and observational studies, published from 2010 to 2020, that evaluated the effectiveness of organisational models for chronic conditions in primary care settings, including home care, community, and general practice. We included 67 international studies out of the 6, 540 retrieved studies. The prevalent study design was the observational design (25 studies, 37.3%), and 62 studies (92.5%) were conducted on the adult population. Four main models emerged, called complex integrated care models. These included models grounded on the Chronic Care Model framework and similar, case or care management, and models centred on involvement of pharmacists or community health workers. Across the organisational models, self‐management support and multidisciplinary teams were the most common components. Clinical outcomes have been investigated the most, while caregiver outcomes have been detected in the minority of cases. Almost one‐third of the included studies reported only significant effects in the outcomes. No sufficient data were available to determine the most effective models of care. However, more complex models seem to lead to better outcomes. In conclusion, in the development of more comprehensive organisational models to manage chronic conditions in primary health care, more efforts are needed on the paediatric population, on the inclusion of caregiver outcomes in the effectiveness evaluation of organisational models and on the involvement of social community resources. As regarding the studies investigating organisational models, more detailed descriptions should be provided with regard to interventions, and the training, roles and responsibilities of health and lay figures in delivering care.